1999
DOI: 10.1046/j.1365-2362.1999.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative inhibitory potential of differently modified antisense oligodeoxynucleotides on hepatitis C virus translation

Abstract: These data demonstrate that terminally modified B-ODN 4 is a potent inhibitor of HCV gene expression in vitro and in HepG2 cell culture and may be valuable for future antiviral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Error bars represent the range of duplicate data points. Previous studies aiming to select ASOs targeting conserved IRES sequences have not identified the 25-to 40-nt region as a priority target region but instead have pointed to other IRES regions, namely, the region around stem-loop III and the region around the initiation ATG codon (1,2,16,27,41). In some of these studies, the authors have omitted the 25-to 40-nt region from the experimental system (1, 2, 16).…”
Section: Discussionmentioning
confidence: 99%
“…Error bars represent the range of duplicate data points. Previous studies aiming to select ASOs targeting conserved IRES sequences have not identified the 25-to 40-nt region as a priority target region but instead have pointed to other IRES regions, namely, the region around stem-loop III and the region around the initiation ATG codon (1,2,16,27,41). In some of these studies, the authors have omitted the 25-to 40-nt region from the experimental system (1, 2, 16).…”
Section: Discussionmentioning
confidence: 99%
“…Such elements can be either viral proteins (NS2-NS3 protease, NS3-NS4A serine proteinase, NS3 RNA helicase, or RNA-dependent RNA polymerase [3,24,34,36]), viral cis-acting RNA elements (internal ribosomal entry site [IRES] antisense oligonucleotides or ribozymes [1,26]), or cellular elements (IFN-␣, ribavirin, and IMP dehydrogenase [EC 1.1.1.205] inhibitors [18,31,41,43]). Current knowledge of the human genome, combined with array technology and pathogen infection models, will likely lead to more defined host-pathogen-related targets for future drug design (17,23).…”
mentioning
confidence: 99%
“…The conserved HCV IRES is a likely target for effective therapeutic intervention. Extensive effort has been devoted to the development of antisense oligonucleotide, [1][2][3][4][5][6][7] ribozyme, [8][9][10] and DNA ribonuclease 11 inhibitors targeting HCV IRES sequences that are accessible for nucleic acid hybridization.…”
mentioning
confidence: 99%